Mobile phone use for pregnancy-related healthcare utilization and its association with optimum antenatal care and hospital delivery in Bangladesh - Gulam Muhammed Al Kibria; Mohammad Rashidul Hashan; Abu Abdullah Mohammod Hanif; Vidhi Maniar; Md Shajedur Rahman Shawon (PLOS Global Public Health, 2023)
Pregnancy-related healthcare utilization is inadequate in Bangladesh, where more than half of pregnant women do not receive optimum number of antenatal care (ANC) visits or do not deliver child in hospitals. Mobile phone use could improve such healthcare utilization; however, limited evidence exists in Bangladesh. We investigated the pattern, trends, and factors associated with mobile phone use for pregnancy-related healthcare and how this can impact at least 4 ANC visits and hospital delivery in the country. We analyzed cross-sectional data from Bangladesh Demographic and Health Survey (BDHS) 2014 (n = 4,465) and 2017–18 (n = 4,903). Only 28.5% and 26.6% women reported using mobile phones for pregnancy-related causes in 2014 and 2017–18, respectively. Majority of the time, women used mobile phones to seek information or to contact service providers. In both survey periods, women with a higher education level, more educated husbands, a higher household wealth index, and residence in certain administrative divisions had greater likelihoods of using mobile phones for pregnancy-related causes. In BDHS 2014, proportions of at least 4 ANC and hospital delivery were, respectively, 43.3% and 57.0% among users, and 26.4% and 31.2% among non-users. In adjusted analysis, the odds of utilizing at least 4 ANC were 1.6 (95% confidence interval (CI): 1.4–1.9) in BDHS 2014 and 1.4 (95% CI: 1.3–1.7) in BDHS 2017–18 among users. Similarly, in BDHS 2017–18, proportions of at least 4 ANC and hospital delivery were, respectively, 59.1% and 63.8% among users, and 42.8% and 45.1% among non-users. The adjusted odds of hospital delivery were also high, 2.0 (95% CI: 1.7–2.4) in BDHS 2014 and 1.5 (95% CI: 1.3–1.8) in BDHS 2017–18. Women with history of using mobile phones for pregnancy-related causes were more likely to utilize at least 4 ANC visits and deliver in health facilities, however, most women were not using mobile phones for that.